POTABILIDADE BACTERIOLÃ“GICA DA ÃGUA DE POÇO OU DE FONTE DA ZONA RURAL DE PIRACICABA - Vertoni, Paulo César; Gallo, Cláudio Rosa; Nogueira, CecÃlia Helena (REVISTA DE AGRICULTURA, 2015)
POTABILIDADE BACTERIOLÃ“GICA DA ÃGUA DE POÇO OU DE FONTE DA ZONA RURAL DE PIRACICABA